Behavioral risk profiling: Measuring loss aversion of individual investors - van Dolder, Dennie; Vandenbroucke, Jurgen (Journal of Banking & Finance, 2024)
Loss aversion has been shown to be a key driver of people's investment decisions. Encouraged by regulators, financial institutions are seeking ways to integrate this behavioral factor into client risk classifications. A critical obstacle is the lack of a valid measurement method for loss aversion that can be straightforwardly incorporated into existing processes. This paper reports on two large-scale implementations of such a method within the risk-profiling application of an established financial institution. We elicit loss aversion for 1,040 employees and 3,740 clients, observing distributions that align with existing findings. Importantly, our results demonstrate that loss aversion is largely independent of the risk-return preferences commonly used for investor classification. Furthermore, the correlations we observe between these two preferences and individuals’ background characteristics align with previous research: loss aversion is strongly correlated with education—higher educated individuals exhibit greater loss aversion—whereas risk aversion is related to gender, age, and financial status—women, older individuals, and those less financially secure are more risk averse. These findings support the conjecture that risk and loss aversion are complementary in capturing investor intent.